Contextualizing Teacher Burnout: A CARL-Based Analysis of Indonesian High School EFL Teachers - Siregar, Fenty Lidya; Henni, Henni (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2026)
Teacher burnout is the most persistent challenge in education. With this in mind,  this study examines the burnout experiences of four Indonesian high school English teachers. The study employed the Context-Action-Result-Learning (CARL) framework developed at the University of Edinburgh and the teacher burnout framework proposed by Sabnani, Dinh, and Siregar (2025). Data collection began by obtaining information about teachers' burnout experiences and coping strategies through a written CARL survey. This was followed by an individual interview with each teacher to gather more information about their burnout experiences. The research findings show that the participants’ burnout contexts varied, ranging from administrative workloads, school-based exam pressures, to pandemic-era challenges, and adaptation. Common patterns emerged in their coping strategies, particularly in leveraging social support, self-care, and professional reflection. The findings reinforce the adaptability of the CARL model while suggesting extensions to include financial and structural stressors in the Context phase and contextual professional learning under the Learning phase. Although the result of the research offers a new perspective on burnout sources and management, this study is limited in its scope and participants. Future research should involve more participants across more varied educational contexts to gain a more comprehensive understanding of teachers’ burnout